Javna uprava v znamenju ljudi - Kovač, Polonca (Teorija in praksa, 2000)
Public administration functions in a complex and constantly changing environment, created mainly by the demands for general growth of work efficiency. At the same time, a greater democratic orientation of public administration is expected, including full participation of employees and consumers of public services in the decision-making processes. Among the ways to approach these requests, the most useful is so called 'New Public Management', as a complex of concepts, which suggest introduction of modern management philosophies and methods to the work of public sector on the pattern from private sector. Introduction of the 'orientation toward the consumers' concept, which is one of the key principles of the new public management, starts with defining potential consumers and their needs and ends with realisation of the established requests. The efficiency of public administration and the quality of public services are thus necessarily conditional on meeting needs and expectations of public service consumers.
Keywords: javna uprava; javni sektor; public sector; management; upravljanje; javne storitve; kvaliteta; uporabniki